2011
DOI: 10.1016/j.aprim.2010.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Dispositivos de coagulometría portátil en el seguimiento y control ambulatorio de la terapia anticoagulante oral: revisión sistemática

Abstract: The analytical-validity related articles show that portable coagulometers have an equivalent effectiveness to conventional coagulometers. Studies that include patient-reported outcomes show that self-monitoring patients, by means of portable coagulometers, have better analytical measurement results and fewer rates of thromboembolic events. Survival was analysed in very few studies; nevertheless, all of these show lower mortality. Similarly, the minority of selected articles includes economic evaluations, altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…In another systematic review, the clinical utility of wearable sensors in patients with Parkinson disease to support clinical decision making was not clear [25]. A 2011 systematic review confirmed no differences between the effectiveness of portable coagulometers and conventional coagulometers in monitoring oral anticoagulation [26].…”
Section: Introductionmentioning
confidence: 99%
“…In another systematic review, the clinical utility of wearable sensors in patients with Parkinson disease to support clinical decision making was not clear [25]. A 2011 systematic review confirmed no differences between the effectiveness of portable coagulometers and conventional coagulometers in monitoring oral anticoagulation [26].…”
Section: Introductionmentioning
confidence: 99%